PENGARUH KINERJA FRONT DESK AGENT TERHADAP KEPUASAN TAMU DI HOTEL ALLIUM NAGOYA BATAM - Rita Rita; Alida Wahyuni (KOMPLEKSITAS: JURNAL ILMIAH MANAJEMEN, ORGANISASI DAN BISNIS, 2020)
AbstractNowadays, employee performance is a determinant of success in a particular industry, company, or organization, if the employee performance is good, then good also the results received, but if bad, it will be poorly received results are not optimal, one of the industries that often find the problem of employee performance is less than the maximum is the hospitality industry, where service becomes the aspect of work, where the performance of employees will affect the services provided to hotel guests, and also affect the hotel guest satisfaction. The author determines the most appropriate Section Front Desk Agent, because the scope of service is very broad, and often problematic to the services provided because the performance of Front Desk Agent is not maximal which makes the guests feel dissatisfied, so the authors do this study aims to determine whether the performance Front Desk Agent has a significant and positive influence on hotel guest satisfaction, where the authors determine the exact location of research because there is an appropriate problem in the hotel Allium Nagoya Batam, in this study the authors use descriptive method Verifikatif to determine the influence, while the population of this study is the hotel guests and took a sample of 50 guests, and collected data from several samples with questionnaires distributed. Based on the results of the data processing questionnaire, which uses a simple linear regression analysis that with the addition of 1% X will increase the satisfaction value = 0.731, and the performance of the Front Desk Agent at the Nagoya Allium Batam hotel has a positive effect on guest satisfaction.